Math, asked by adityayadav110047, 11 months ago

find the roots of equation x^2+x-p(p+1),where p is constant​

Answers

Answered by ekhlaq
5

Answer:

x =  \frac{ - 1 + (2p + 1)}{2}

x =  \frac{ - 1 - (2p + 1}{2}

Step-by-step explanation:

 {x}^{2} + x  - p(p + 1)

Using quadratic formula:

x =  \frac{ - 1 (+ -)  \sqrt{1 + 4( {p}^{2} + p } }{2}

x =  \frac{ - 1( +  - ) \sqrt{4 {p}^{2} + 4p + 1 } }{2}

x =   \frac{ - 1( +  - ) \sqrt{ {2p + 1}^{2} } }{2}

x =   \frac{ - 1( +  - )(2p + 1)}{2}

(+-) means plus or minus.

Mark me as brainliest.

Similar questions